A rapid real-time quantitative PCR assay to determine the minimal inhibitory extracellular concentration of antibiotics against an intracellular Francisella tularensis Live Vaccine Strain - Aloni-Grinstein, Ronit; Shifman, Ohad; Lazar, Shlomi; Steinberger-Levy, Ida; Maoz, Sharon; Ber, Raphael (Frontiers in Microbiology, 2015)
Francisella tularensis is a highly virulent facultative intracellular bacterium. The lack of a safe and efficient vaccine makes antibiotics the preferred treatment. F. tularensis antibiotic susceptibility tests are based on the in vitro standard CLSI-approved microdilution method for determining the MIC. However, limited data are available regarding the minimal inhibitory extracellular concentration (MIEC) needed to eradicate intracellular bacteria. Here, we evaluated the MIEC values of various WHO-recommended antibiotics and compared the MIEC values to the established MICs. We describe a rapid 3-hour qPCR intracellular antibiogram assay, which yields comparable MIEC values to those obtained by the classical 72-hour cfu assay. This rapid qPCR assay is highly advantageous in light of the slow growth rates of F. tularensis. Our results showed that the MIECs obtained for doxycycline, chloramphenicol and ciprofloxacin were indicative of intracellular activity. Gentamicin was not effective against intracellular bacteria for at least 32 hours post treatment, raising the question of whether slow-penetrating gentamicin should be used for certain stages of the disease. We suggest that the qPCR intracellular antibiogram assay may be used to screen for potentially active antibiotics against intracellular F. tularensis as well as to detect strains with acquired resistance to recommended antibiotics.